Assessment of genetic diversity in Chaetomium globosum, a potential biocontrol agent by amplified fragment length polymorphism - V.G. MALATHI, RASHMI AGGARWAL*, RENU, P. SRINIVAS (Indian Phytopathology, 2010)
Chaetomium globosum has been identified as a potential biocontrol agent against Bipolaris sorokiniana causing spot blotch of wheat. Five isolates of C. globosum (Cg1, Cg5, Cg6, Cg7, and Cg8) exhibiting encouraging biocontrol properties were studied for their genetic variation using Amplified Fragment Length Polymorphism (AFLP) analysis. The protocols for speedy extraction of DNA, polymerase chain reaction conditions and AFLP reaction were optimized. Digestion products of EcoRI and MseI enzymes, ligated with double standard adapters were pre-amplified with EcoRI (E) and MseI (M) primers. After labeling EcoRI primer with selective base AC with 32P ATP, selective amplification was carried out with four primer combinations, E-AC/M-A, E-AC/M-C, E-AC/M-G and E-AC/M-T. A total of 517 AFLP amplified products were obtained, out of which 476 were polymorphic. The number of fragments amplified for each of the five isolates ranged from 124-137 having 5-15 monomorphic fragments for each primer pair combination. Genetic similarities of AFLP profiles were estimated on the basis of Jaccard’s coefficient. Each isolate was clearly identified and separated from others based on the similarity index values indicating the presence of genetic diversity at molecular level. These similarity coefficients were subjected to Unweighted Pair Group Method on Arithmetic Averages (UPGMA) using paired matrix values with SPSS version 9.0. The dendrogram generated consisted of two very distinct clusters; first cluster having three isolates Cg 6, Cg 7 and Cg 8 which was further separated into two groups. Cg6 was clearly distinct from other two closely related isolates Cg7 and Cg8 (96%) in first cluster. Second cluster comprised of distinctly related Cg 1 and Cg 5 isolates (28%). This is the first report of using AFLP technique for studying the variability among the isolates of biocontrol agent, Chaetomium globosum.